Cultural Diplomacy and Soft Power: The Impact of South Korea’s Pop Culture on China and the World - Jiang, Zhiqi (University of the Witwatersrand, Johannesburg, 2024)
This research paper, titled "Cultural Diplomacy and Soft Power: The Impact of South Korea’s Pop Culture on China and the World" is submitted by Zhiqi Jiang on August 16, 2024, as a Master’s Research Report in International Relations. It examines the extent to which South Korea’s pop cultural diplomacy has challenged China’s cultural dominance in East Asia and contributed to South Korea’s rise in global soft power since the 1990s. By contrasting the cultural diplomacy strategies of China and South Korea and investigating the achievements of South Korea’s pop cultural diplomacy in economics, international organizations, and foreign policies, the study argues that South Korea’s strategic promotion of its pop culture, including K-pop, K-dramas, and films, has significantly enhanced its soft power. This influence manifests in South Korea’s ability to shape public opinion and influence economic and foreign policies in and with China. Additionally, South Korea has leveraged global economic gains and diplomatic influence through celebrity youth diplomacy to further strengthen its international soft power. The findings highlight the critical role of pop cultural diplomacy in international relations, providing insights for nations seeking to improve their global standing.
A research report Submitted in fulfillment of the requirements for a Master of Arts in International Relations, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; cultural diplomacy; soft power; South Korea; China; pop culture; pop culture diplomacy; K-pop; Hallyu; Korean wave; SDG-17: Partnerships for the goals